THE CRITICAL EVALUATION OF A FACULTY OF EDUCATION WEB SITE BY COMPUTER TEACHER CANDIDATES - (:unkn) unknown (ELSEVIER SCIENCE BV, 2012)
The aim of this research is to investigate the Web site evaluation skills of computer teacher candidates as they assess the Trakya University Faculty of Education web site in terms of visual design, structure and navigation. The research utilizes a Web Site Evaluation form and a semi-structured interview in order to collect the required data. The analysis of the quantitative data has been carried out via descriptive statistical techniques; with the frequency and percentage distribution figures for each item given in charts; whereas the analysis of the qualitative data has been carried out through descriptive analysis techniques. It was concluded from the study that the computer teacher candidates found the faculty web site to be easy to use and fluid in terms of navigation and they reported that the site works as intended and without problems. However, it was also reported by the teacher candidates, that the faculty web site had neither a customized site search engine nor a promotional video and that, the promotional images needed a more professional touch in order to have a stronger effect on visitors. Another conclusion was that the computer education teacher candidates tended to pay attention on issues like color schemes in the visual design of a web site and that they preferred not having too much visual detail or animations within similar websites. (C) 2012 Published by Elsevier Ltd. Selection and/or peer-review under responsibility of The Association of Science, Education and Technology
Keywords: CEIT; Web site evaluation; Web design; Education Faculty